The Gemini Contenders - Ludlum, Robert, 1927-2001 (New Yrok A Dell Books, 1976)
A train winds through Italy towards the Alps with a precious cargo on board. The cargo is a box containing papers that could destroy the Christian world. Savarone is responsible for the documents' safety but he's marked for death by the Nazis.
Keywords: Brothers -- Italy